Parental Readiness: The Relationship Between Knowledge and Emotional Well-Being in Mothers - Sintia Agita Putri; Riski Hediya Putri (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2026)
Background & Objective: Pregnancy is an important phase that requires comprehensive readiness, including physical, emotional, and knowledge aspects, to prepare for the role of parenthood. Pre-survey findings indicated unpreparedness in emotional, financial, and knowledge aspects, which may affect the parenting process after childbirth. This study aimed to determine the relationship between knowledge factors and the emotional condition of pregnant women with readiness for parenthood at RSU Mitra Mulia Husada. Methods: This study used a quantitative design with a cross-sectional approach. The sample consisted of 38 pregnant women selected using a purposive sampling technique. The study was conducted from October 1 to October 30, 2025, at RSU Mitra Mulia Husada. Data analysis was performed using the Gamma test. Results: The results showed that the majority of respondents had a high level of knowledge (52.6%) and moderate readiness for parenthood (55.3%), while most respondents also had a moderate level of emotional readiness (63.2%). Statistical analysis demonstrated a significant relationship between knowledge and readiness for parenthood with a p-value = 0.000. Meanwhile, emotional condition showed no significant relationship with readiness for parenthood with a p-value = 0.684. Conclusion: These findings indicate that knowledge readiness plays a more important role in preparing pregnant women for their new role as parents compared to emotional aspects. Therefore, prenatal education and psychological support need to be strengthened to improve pregnant women’s readiness in carrying out child-rearing responsibilities.